The effect of CuPc nanostructures on the photo and electrophysical characteristics of the active layer P3HT/PCBM - Aimukhanov, A.K.; Ilyassov, B.R.; Zeinidenov, A.K.; Zavgorodniy, A.V. (Eurasian Journal of Physics and Functional Materials, 2019)
The paper presents the results of a study of the influence of copper phthalocyanine (CuPc) nanostructures on the generation and transfer of charge carriers in the photoactive P3HT/PCBM layer. It was shown that the observed broadening and the shift in the maxima of the absorption spectra of P3HT/PCBM upon the addition of nanostructures to the polymer are associated with an increase in the degree of crystallization of the film. Using the method of impedance spectroscopy, it was found that CuPc nanostructures enhance the rate of recombination of charge carriers, which is probably due to the formation of surface defects. These defects are electron capture centers through which carrier recombination occurs. Despite that polymer solar cells with CuPc nanostructures have enhanced recombination rate, their photovoltaic properties were better than pure polymer solar cells due to enhanced light absorption and increased film conductivity.
Keywords: P3HT/PCBM; copper phthalocyanine; nanoparticles; nanowires; IVC; impedance spectroscopy